2007
DOI: 10.1088/0953-8984/20/03/035212
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic molecular properties of one-electron double quantum rings under magnetic fields

Abstract: Abstract.The molecular states of conduction electrons in laterally coupled quantum rings are investigated theoretically. The states are shown to have a distinct magnetic field dependence, which gives rise to periodic fluctuations of the tunnel splitting and ring angular momentum in the vicinity of the ground state crossings. The origin of these effects can be traced back to the Aharonov-Bohm oscillations of the energy levels, along with the quantum mechanical tunneling between the rings. We propose a setup usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 48 publications
(113 reference statements)
1
11
0
Order By: Relevance
“…Also, the inter-ring coupling is responsible for the reduction of persistent currents and magnetic dipole moments in a two-dimensional array of multiple QRs 19 and, as proposed in ref. 20 , even in the absence of the net flux Aharonov-Bohm oscillations can be obtained in QR molecules. In addition, calculations of persistent currents in a QRs modeled by the Holstein-Hubbard-Rashba 21 have demonstrated that the electron-phonon interactions reduce the persistent current, while the Rashba coupling enhances it and the temperature smoothens the persistent current curve.…”
Section: Introductionmentioning
confidence: 92%
“…Also, the inter-ring coupling is responsible for the reduction of persistent currents and magnetic dipole moments in a two-dimensional array of multiple QRs 19 and, as proposed in ref. 20 , even in the absence of the net flux Aharonov-Bohm oscillations can be obtained in QR molecules. In addition, calculations of persistent currents in a QRs modeled by the Holstein-Hubbard-Rashba 21 have demonstrated that the electron-phonon interactions reduce the persistent current, while the Rashba coupling enhances it and the temperature smoothens the persistent current curve.…”
Section: Introductionmentioning
confidence: 92%
“…33 Inter-ring tunneling for a single-electron states in a pair of laterally coupled InGaAs rings was recently studied. 29 The authors considered etched rings with very low indium concentration ͑5%͒ producing very shallow cavities of 50 meV depth. Even for rings that are so shallow, a very small inter-ring distances of 3 nm had to be assumed 29 for the discussion of the tunnel coupling.…”
Section: Theorymentioning
confidence: 99%
“…29 The authors considered etched rings with very low indium concentration ͑5%͒ producing very shallow cavities of 50 meV depth. Even for rings that are so shallow, a very small inter-ring distances of 3 nm had to be assumed 29 for the discussion of the tunnel coupling. The main results of the present paper were obtained for interring distance greater than 10 nm.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…These experimental results claim the need to investigate how the coupling between the rings in CDQRs can be influenced both externally and internally. Internally, it has been demonstrated to be realizable by varying the inter-ring distance and aluminium concentration during the calculations of few-electron 20 and impurity-related linear and non-linear optical absorption spectrum 21 respectively, while externally it can be done by applying magnetic and electric fields 22 27 and with hydrostatic pressure 28 as well.…”
Section: Introductionmentioning
confidence: 99%